Pengaruh faktor kepuasan pengguna terhadap kesetiaan jenama dalam kalangan pengguna telefon pintar - Osman, Syuhaily; Ishak, Farah Liyana (Malaysian Consumer and Family Economics Association, 2019)
The main purpose of this study is to investigate the influential factors of consumer satisfaction (brand, quality and price) towards brand loyalty among smartphone users at UPM, Serdang. A total of 200 respondents were participated in this study which were selected through the systematic random sampling method. A set of selfadministered questionnaires was distributed to the respondents. Pearson's correlation test was used to determine the relationship between factors of consumer satisfaction in terms of brand, quality and price towards the brand loyalty in smartphone purchasing behavior. The results showed that all independent variables have a positive relationship which were brand (r = .599, p = .000), quality (r = .243, p = .001) and price (r = .454, p = .000). Besides that, multiple regression analysis results indicated that brand (Beta= 0.489; p = 0.000) was the strongest predictor towards brand loyalty in smartphones and the quality factor does not have significant relationship towards brand loyalty in smartphones when testing were conducted simultaneously. This findings give implications for manufacturers, traders, consumers and researchers to determine to what extent the influential factors of consumer satisfaction in terms of brand, quality and price towards the brand loyalty in smartphones.